Workbook for quantitative business analysis / Nur Intan Syafinaz Ahmad ...[et al.] - Ahmad, Nur Intan Syafinaz; Semil @ Ismail, Ghazali; Abdul Karim, Zokree; Muda @ Yusof, Nazuha; Wan Abdullah, Wan Karomiah (Faculty Of Computer And Mathematical Sciences, 2021)
This Workbook for Quantitative Business Analysis is especially written for all students taking the quantitative analysis subject. The contents of the book are based on the basic topic of quantitative analysis relies on using mathematics to solve business issues with measurements based on verifiable information. This book is suitable for students who are taking diploma or degree in higher institution level. This book contains seven chapters. In each chapter the introduction, definition, and steps are clearly stated with suitable guided and hands-on examples to ensure students clearly understood the concepts of each topic. At the end of each chapter, exercise are provided with full answer to provide full guidance for students to solve the problem. The authors would like to express their gratitude and appreciation towards all their colleagues and peers who contributed directly and indirectly in successful publication of this book. The authors would like to wish all the best to all students undertaking this subject and hopefully they will success in their study.